Experimental Study of Imbibition Within Core Chips of Shale in Ordos Basin - Wu, Jiang; Mu, Lijun; Ren, Dazhong; Liu, Jin; Hui, Honggang; Wang, Zhenze (Frontiers in Physics, 2022)
The main exploring technology of No.7 Yanchang Formation of the Triassic reservoir in the Ordos Basin adopts quasi-natural downhole energy driven by volume fracturing, and the region production thus cannot be improved by an injection well network. Enhanced oil recovery (EOR) has been carried out through an enhanced imbibition process during reservoir stimulation work. To further understand the oil-water displacement mechanism, a thin-cut chips of shale imbibition experimental study was carried out. Simultaneously, nuclear magnetic resonance (NMR) changes of the fluid within the pores of chips were measured. This method was used to evaluate the application effect of imbibition surfactant in use, and the field practice was compared and analyzed by means of a chemical tracer among dozens of clusters in the same horizontal well.